Developing Sustainable Business Practices in SMEs: A Community Outreach Initiative for Environmental and Economic Resilience - Aripin (Global Writing Academica Researching and Publishing, 2022)
Small and medium enterprises (SMEs) play a vital role in the economy but often face challenges in implementing sustainable business practices. Constraints such as limited resources, access to information, and unsupportive regulations make it difficult for SMEs to switch to more environmentally friendly practices. In addition, community initiatives and local support are important factors in encouraging the adoption of sustainable practices. This study aims to explore effective strategies that can help SMEs switch to sustainable business practices. This study uses a qualitative approach by collecting data from various reliable sources and analyzing them in depth. The conclusion of the study shows that the implementation of sustainable business practices by SMEs can reduce negative impacts on the environment, such as reduced carbon emissions and better waste management. In addition, these practices also increase the efficiency and productivity of SME operations. The adoption of sustainability strengthens the long-term resilience of SMEs to market changes and environmental challenges. Positive impacts are also felt by local communities, including improved quality of life and economic stability. Support from proactive government policies, adequate infrastructure, and access to green financing are critical to the success of this transition.